Формування змісту ранньої іншомовної освіти в Україні наприкінці ХХ - на початку ХХІ ст. - Юдіта Павлович; Pavlovics Judit; Judit Pavlovich („RIK-U” Kft., 2019)
Анотація. У статті розглядається проблеми формування змісту ранньої іншомовної освіти в Україні наприкінці ХХ та на початку ХХІ ст. Схарактеризовано особливості мовної політики України та розвиток змісту ранньої іншомовної освіти за останні роки. Особливу увагу приділено характеристиці мовної складової Базового навчального плану розвитку освіти України. Визначено чинники, які позитивно вплинули на розвиток змісту ранньої іншомовної освіти в країні.

Abstract. The article deals with the problem of early foreign language education content formation in Ukraine at the end of the 20th and at the beginning of the 21st century. The main peculiarities of language policy in Ukraine and the development of early foreign language education content during the last years have been characterized. Special attention has been paid to the language component of the Basic educational plan of schooling development in these countries. The main factors that influenced greatly the early foreign language content development in the countri have been determined.
A korai idegennyelv-oktatás tartalmának alakulása a XX. század végén és a XXI. század elején
Early foreign language education content formation in Ukraine at the end of the 20th and at the beginning of the 21st century
https://kmf.uz.ua/wp-content/uploads/2019/04/Final-Pedagogical_conf_2019_03_28-29.pdf
https://opac3.brff.monguz.hu:443/en/record/-/record/bibBRF00007073
Keywords: рання іншомовна освіта; реформування; зміст; мовна політика; навчальний план; комунікативний підхід